Analyzing The Relationship Between Marketing Public Relations, Digital Marketing, Marketing Mix, Customer Service, and Customer Loyalty - Yuni Sara; Nuril Khusni Al Amin; Nida Safira (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2023)
This study aims to investigate the intricate relationship among marketing public relations, digital marketing, marketing mix, customer service, and customer loyalty within the contemporary business landscape. Employing a qualitative research design, the study utilizes purposive sampling to gather data from a diverse range of industry experts, marketers, and consumers. Data analysis involves thematic analysis to unveil patterns, themes, and insights from the collected data. The findings shed light on the nuanced interactions among marketing public relations, digital marketing strategies, elements of the marketing mix, quality customer service provision, and its impact on fostering customer loyalty. This research contributes to a deeper understanding of the dynamic marketing ecosystem, offering valuable insights for businesses aiming to enhance customer engagement and loyalty in the digital age.